Zirconium (IV) Acetylacetonate: Ring-Opening Initiator Mediating One-Step Synthesis of Biodegradable Polyacids - Piotr Dobrzyński; Małgorzata Pastusiak; Joanna Jaworska; Bożena Kaczmarczyk; Michał Kwiecień; Michał Kawalec (Advances in Polymer Technology)
Biodegradable polyacid is obtained in one-step ring-opening polymerization (ROP) of carboxylic-acid-functionalized six-membered cyclic carbonate mediated with zirconium (IV) acetylacetonate. Exemplary copolymers with L,L-lactide are described as well. Moreover, zirconium (IV) acetylacetonate is found to be active catalyst of trimethylene carbonate (TMC) ROP in presence of carboxylic acid yielding PTMC end-capped with the acid derivative. Polymerization mechanism is hypothesized demonstrating possibilities of the method in work-saving polycation synthesis and one-step method of conjugate synthesis of well-known biocompatible polyesters and polycarbonates.